PENGARUH KESESUAIAN TUGAS, INSENTIF, EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PENGGUNA SISTEM INFORMASI AKUNTANSI PADA LPD DI KECAMATAN MENGWI - Ni Nyoman Ayu Trisna Dewi; Ni Komang Sumadi (Hita Akuntansi dan Keuangan, 2021)
This study aims in this study to determine the effect of task suitability, incentives, effectiveness of SIA implementation, work environment influence on employee performance on employee performance of SIA users. The population in this study were all employees of SIA users in LPD, Mengwi District. The sample used in this study was 120 respondents. The data analysis techniques used in this study were the validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the research results it can be seen that: (1) task suitability has a significant positive effect on employee performance, where the coefficient value of regression is 0.289 and sig 0.011. (2) the incentive has a significant positive effect on employee performance, where the regression coefficient value is 0.427 and sig 0.001. (3) the effectiveness of the implementation of SIA has a significant positive effect on employee performance, where the regression coefficient value is 0.358 and sig is 0.005. (4) the work environment has a significant positive effect on employee performance, where the regression coefficient value is 0.185 and sig 0.004. The magnitude of the influence of the variable task suitability, incentives, effectiveness of SIA implementation, work environment on employee performance is 50.7%.